Release of extracellular DNA influences renal ischemia reperfusion injury by platelet activation and formation of neutrophil extracellular traps - Jansen, Marcel P B; Emal, Diba; Teske, Gwendoline J D; Dessing, Mark C; Florquin, Sandrine; Roelofs, Joris J T H (Kidney international, 2017)
Acute kidney injury is often the result of ischemia reperfusion injury, which leads to activation of coagulation and inflammation, resulting in necrosis of renal tubular epithelial cells. Platelets play a central role in coagulation and inflammatory processes, and it has been shown that platelet activation exacerbates acute kidney injury. However, the mechanism of platelet activation during ischemia reperfusion injury and how platelet activation leads to tissue injury are largely unknown. Here we found that renal ischemia reperfusion injury in mice leads to increased platelet activation in immediate proximity of necrotic cell casts. Furthermore, platelet inhibition by clopidogrel decreased cell necrosis and inflammation, indicating a link between platelet activation and renal tissue damage. Necrotic tubular epithelial cells were found to release extracellular DNA, which, in turn, activated platelets, leading to platelet-granulocyte interaction and formation of neutrophil extracellular traps ex vivo. Renal ischemia reperfusion injury resulted in increased DNA-platelet and DNA-platelet-granulocyte colocalization in tissue and elevated levels of circulating extracellular DNA and platelet factor 4 in mice. After renal ischemia reperfusion injury, neutrophil extracellular traps were formed within renal tissue, which decreased when mice were treated with the platelet inhibitor clopidogrel. Thus, during renal ischemia reperfusion injury, necrotic cell-derived DNA leads to platelet activation, platelet-granulocyte interaction, and subsequent neutrophil extracellular trap formation, leading to renal inflammation and further increase in tissue injury.